Importance of the Correlation between Width and Length in the Shape Analysis of Nanorods: Use of a 2D Size Plot To Probe Such a Correlation. Issue 35 (27th July 2016) - Zhao, Zhihua; Zheng, Zhiqin; Roux, Clément; Delmas, Céline; Marty, Jean‐Daniel; Kahn, Myrtil L.; Mingotaud, Christophe
Abstract: Analysis of nanoparticle size through a simple 2D plot is proposed in order to extract the correlation between length and width in a collection or a mixture of anisotropic particles. Compared to the usual statistics on the length associated with a second and independent statistical analysis of the width, this simple plot easily points out the various types of nanoparticles and their (an)isotropy. For each class of nano‐objects, the relationship between width and length (i.e., the strong or weak correlations between these two parameters) may suggest information concerning the nucleation/growth processes. It allows one to follow the effect on the shape and size distribution of physical or chemical processes such as simple ripening. Various electron microscopy pictures from the literature or from the authors′ own syntheses are used as examples to demonstrate the efficiency and simplicity of the proposed 2D plot combined with a multivariate analysis. Abstract : 2D or not 2D : Analysis of nanoparticle size through a simple 2D plot is used to extract the correlation between length and width in a collection or a mixture of anisotropic particles. Various electron microscopy pictures are used as examples to demonstrate the efficiency and simplicity of the proposed 2D plot combined with a multivariate analysis.